2018
DOI: 10.3201/eid2410.172079
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection during Pregnancy and Effects on Early Childhood Development, French Polynesia, 2013–2016

Abstract: Congenital Zika virus syndrome consists of a large spectrum of neurologic abnormalities seen in infants infected with Zika virus in utero. However, little is known about the effects of Zika virus intrauterine infection on the neurocognitive development of children born without birth defects. Using a case-control study design, we investigated the temporal association of a cluster of congenital defects with Zika virus infection. In a nested study, we also assessed the early childhood development of children recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…The majority of confirmed cases of ZIKV occurred in the second and third trimesters of gestation. However, when analyzing the trimester of ZIKV infection in children born with microcephaly, we noticed that most of them became infected in the first trimester of pregnancy, which is compatible with the literature, since pregnant women with infection in the first trimester have the most severe cases, as well as an increased risk of microcephaly in their conceptuses 11,12,13 .…”
supporting
confidence: 89%
“…The majority of confirmed cases of ZIKV occurred in the second and third trimesters of gestation. However, when analyzing the trimester of ZIKV infection in children born with microcephaly, we noticed that most of them became infected in the first trimester of pregnancy, which is compatible with the literature, since pregnant women with infection in the first trimester have the most severe cases, as well as an increased risk of microcephaly in their conceptuses 11,12,13 .…”
supporting
confidence: 89%
“…Vermian hypoplasia and global cerebellar hypoplasia were reported in 42% and 21% to 82% of CZS cases, respectively . The brainstem can also be hypoplastic or dysplastic and is associated with extra‐cerebral abnormalities such as swallowing disorders and hydramnios (25%) as well as partial immobilization or arthrogryposes (10%‐25%) …”
Section: Congenital Zikv Syndromementioning
confidence: 99%
“…Another study reported feeding challenges, sleeping difficulties, severe motor impairment, vision and hearing abnormalities, and/or seizures disorders in all 18‐ to 24‐month old infants born with CZS . Long‐term sequelae, particularly regarding neuro‐development and cognitive function of these infants, however, remain insufficiently investigated …”
Section: Congenital Zikv Syndromementioning
confidence: 99%
See 2 more Smart Citations